Ictal Epileptic Headache: When Terminology Is Not a Moot Question - Parisi, Pasquale; Paolino, Maria Chiara; Raucci, Umberto; Della Vecchia, Nicoletta; Belcastro, Vincenzo; Villa, Maria Pia; Striano, Pasquale (Frontiers in Neurology, 2019)
The relationship between headache and epilepsy is much complicated and although the nature of this association is not yet fully clear, several plausible explanations have been proposed. In the last few years, it has been progressively introduced the concept of the “ictal epileptic headache” that was included in the recently revised International Classification of Headaches Disorders 3rd edition (ICHD-3-revised). When the diagnostic criteria for ictal epileptic headache (IEH) were published in 2012, the authors deliberately and consciously chose to adopt restrictive criteria that probably underestimate the phenomenon; the reasons for this “restrictive perspective of the phenomenon” were related to the reluctance, both by doctors and experts in the specific field of research, to accept this possible (and probably less rare than previously thought), complete overlap between epilepsy and headache. These criteria have not been fully taken into account in the recent ICHD-3 revision published in 2018, thus creating confusion among both, physicians and experts in this field. The Authors underline the importance to strictly apply the original IEH criteria explaining the reasons through the analysis of the clinical, historical, epidemiological and pathophysiological characteristics of the IEH itself. In addition, we discuss the neurophysiopathological links, and the possible classification of the most of these epileptic events among the “autonomic seizure”. The neurophysiological and EEG peculiar aspects that IEH have in common with the autonomic seizures of the Panayiotopoulos syndrome are also discussed.